Immunophenotype of the macrophage population in fibrous, cavernous pulmonary tuberculosis - E. P. Golubinskaya; T. G. Filonenko; A. V. Kubyshkin; Yu. A. Yermola; M. A. Kalfa; A. V. Gerashchenko; T. V. Kramar (Бюллетень сибирской медицины, 2019)
Objective: to study the immunophenotype of the macrophage population and the mechanisms of their vectorial redistribution in fibrous cavernous pulmonary tuberculosis.Materials and methods. The material for the study was fragments of the fibrous cavern wall and pericavernous lung tissue of the dead or surgical patients diagnosed with fibrous cavernous tuberculosis (n = 163). All patients were divided into 2 main groups: patients with active bacteria excretion (MTB+, n = 84) and patients with clinical abacillation (MTB–, n = 79) for immunohistochemistry with a panel of markers for: macrophages and histiocytes – CD68; vascular growth factor A – VEGF-A; T-helpers – CD4, and T-cytotoxic lymphocytes – CD8.Results. Following the analysis of CD68 expression, the population heterogeneity of macrophages was revealed depending on the intensity of the cytoplasmic reaction, functional activity, localization and quantitative characteristics. Three groups were identified: highly active, moderately active and weakly active. Based on the reaction with vascular growth factor A, it was determined that VEGF+ cells correspond to weakly active CD68+ macrophages and are located on the border between the specific granulation tissue and fibrous layer as well as in the pericavernous zone and intact lung tissue with a statistically significant predominance in patients with MTB– (p < 0.05). Regardless of the scope of bacterial secretion, the number of VEGF+ cells in the lymphoid follicle zone directly correlates with that of CD68+ macrophages in the pericavernous zone (R = 0.68) and indirectly correlates with the number of diffusely scattered VEGF+ cells in the fibrous capsule (R = –0.75). In the meantime, CD68+/VEGF+ are visualized in the zone of CD8+ T-lymphocytes, and CD68+/VEGF- – in the zone of CD4+ cell clusters. Such correlation indicates the redistribution of macrophages into type 2, which has a remodeling effect on the surrounding tissues with the potentiating participation of lymphoid cells.